Diseño de un banco de pruebas que permita el diagnóstico de fallas en motores de arranque antes de su ensamblaje en el automóvil, para la electromecánica Herrera ubicada en el sector de Lasso, provincia de Cotopaxi, en el período académico mayo 2020 – septiembre 2020. - Andrade Huertas, Cristian Patricio (2020)
In recent years in Ecuador, the automobile sector has increased, so that light vehicles represent 87% of the units that circulate in the country, the province of Cotopaxi, being in the center of the country, is an artery for the union of the coast and sierra regions, therefore, the number of vehicles circulating on the main highways is high, this is the reason that users are forced to look for a reliable maintenance service. The electrical system tends to be one of the most common to suffer damage. The initial ignition system consists of a starter motor which is the second most common case of failure due to the fact that in maintenance artisanal verification techniques are used, which leads to an unreliable process and excessive maintenance time, as well The need arises to design a test bench that allows the diagnosis of faults in starter motors before their assembly in the car, in order to reduce maintenance time, generate a more reliable process and achieve by verifying the values ratings of the starter motor diagnose failures before re-assembly which leads to a decrease in maintenance time and in turn generates quality work for Electromecánica Herrera located in the Lasso sector, Cotopaxi province. The results obtained from this technological proposal through simulation allowed to establish that the reduction of maintenance time is 62.5% with respect to conventional methods, in addition through simulation it is possible to graphically observe the nominal values of voltage and currents of the motor. start.